Stress and sex determination in fish: From brain to Gonads - Castañeda Cortes, Diana Carolina (2020)
Fish present remarkable malleability regarding gonadal sex fate. This phenotypic plasticity enables an organism to adapt to changes in the environment by responding with different phenotypes. The gonad and the brain present this extraordinary plasticity. These organs are involved in the response to environmental stressors to direct gonadal fate, inducing sex change or sex reversal in hermaphroditic and gonochoristic fish, respectively. The presence of such molecular and endocrine plasticity gives this group a large repertoire of possibilities against a continuously changing environment, resulting in the highest radiation of reproduction strategies described in vertebrates. In this review, we provide a broad and comparative view of tremendous radiation of sex determination mechanisms to direct gonadal fate. New results have established that the driving mechanism involves early response to environmental stressors by the brain plus high plasticity of gonadal differentiation and androgens as by-products of stress inactivation. In addition to the stress axis, two other major axes – the hypothalamic-pituitary-gonadal axis and the hypothalamic-pituitary-thyroid axis, which are well known for their participation in the regulation of reproduction – have been proposed to reinforce brain-gonadal interrelationships in the fate of the gonad.